Efek Harga dan Kualitas Layanan Terhadap Kepuasan Konsumen (Studi Pada Customer Toyota Avanza) - Ibrahim, Darmawansah (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
This research was conducted with the aim to determine the effect of price and service quality on consumer satisfaction in car users Toyota Avanza Pt. Hadji Kalla Branch. Urip Sumoharjo Makassar This study uses a questionnaire to be given to consumers who use Toyota Avanza cars, as many as 52 samples from some of the existing population. Data were analyzed using the SPSS Version 16 program. The results of this study indicate that price has a significant effect on customer satisfaction in purchasing a Toyota Avanza car, service quality has a significant effect on customer satisfaction in purchasing a Toyota Avanza car, price and service quality have a significant effect on customer satisfaction in purchasing Toyota Avanza car. The results of multiple linear regression analysis between price and service quality simultaneously have a significant influence on customer satisfaction in purchasing a Toyota Avanza car.